LINGUISTIC EXPRESSION WITH REFERRENCE TO SEMIOTIC IN ULOS OF WEDDING CEREMONY OF BATAK TOBA - Hendro Doglas Simamora and Zainuddin (LINGUISTICA, 2017)
This study was deal with linguistic expression, in semiotics of ulos in wedding ceremony of batak toba. This research used qualitative method which concerned with developing explanations of experience or on data. The source of the data was taken from the ulos in wedding ceremony of batak toba, and relevant with the transcript of interviewing by three informants with some criterias, that is the most dominant population in three different surename in Tarutung, at the age of 45 to 55 years old and have the recognition from each surename. The instruments that is used in this study was tape recorder, camera, and also the book which relevant to the data. In technique of analyzing data, descriptive qualitative data analysis stage is identifying the ornament, reducing the ornament which are not relevant, classifying, interpreting, analyzing and concluding the findings. There are three kinds of ulos used in wedding ceremony of Batak Toba, they are ulos ragidup, ulos ragihotang, and ulos sadum. Each ulos have topi sokkar which explain that everything in this world have the limit and the color depend to the ceremony that is performed. In ulos ragidup, there are hatir symbolized of wealth, sigumang symbolized the hope of the giver of this ulos for the receiver to works right and efficient also, batu ni ansimun symbolizing the health, sisik ni ikan symbolizing a good life, tidy life, even in a crowded of life, and also jungkit symbolizing in having an organized life well. In ulos ragihotang there are unok-unok, symbolized be a wise person like the humus, and jungkit. In ulos sadum, there is torna where this symbol to remind the people that Batak people come from mountain.